Safety and efficacy of fenproporex for obesity treatment: a systematic review - Francisco José Roma Paumgartten; Sabrina Schaaf Teixeira Costa Pereira; Ana Cecilia Amado Xavier de Oliveira (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To evaluate clinical evidence on the safety and efficacy of fenproporex for treating obesity. METHODS MEDLINE, LILACS and Cochrane Controlled Trials Register were searched as well as references cited by articles and relevant documents. Two authors independently assessed the studies for inclusion and regarding risk of bias, collected data, and accuracy. Eligible studies were all those placebo-controlled that provided data on the efficacy and safety of Fenproporex to treat obesity. RESULTS Only four controlled studies met the inclusion criteria. One randomized, placebo-controlled trial on Fenproporex was found on electronic databases. Three placebo-controlled studies (in non-indexed journals) were identified by hand-searching. Patients with cardiovascular and other comorbidities were excluded in all studies. Trials lasted from 40 to 364 days and doses ranged from 20 to 33.6 mg/d. All controlled studies found that weight loss among Fenproporex-treated patients was greater than that produced by the placebo, but drug effect was modest. Fenproporex produced additional weight reductions of 4.7 kg (one year), 3.8 kg (six months) and 1.55 kg (two months) in average, in relation to diet and exercise only (three trials). Insomnia, irritability, and anxiety were the most frequently reported side effects in the four studies. CONCLUSIONS There is a paucity of randomized, placebo-controlled trials on Fenproporex and those identified here present major methodological flaws. These studies suggest that Fenproporex is modestly effective in promoting weight loss. Nonetheless, they failed to provide evidence that it reduces obesity-associated morbidity and mortality. Data from these studies are insufficient to determine the risk-benefit profile of Fenproporex. Abuse potential and amphetamine-like adverse effects are causes for concern.